The increased breast mammographic density as an adverse effect of menopausal hormonal therapy - Paszkowski, Tomasz; Pertyński, Tomasz; Drop, Andrzej; Jaśkiewicz, Janusz (Menopause Review/Przegląd Menopauzalny, 2006)
The influence of menopausal hormonal therapy (HT) on the breast remains one of the crucial aspects of the menopausal medicine. In this context the jatrogenic deterioration of the mammographic examination sensitivity due to the increased mammographic breast density (MBD) gains special importance. This problem is analyzed in the paper from the multidisciplinary point of view of a gynecologist, radiologist and a surgeon. The increased MBD in the course of HT constitutes an extremely important clinical problem which is currently being widely discussed worldwide. The high MBD affects the breast cancer risk, hampers the interpretation of the mammographic examination and decreases both the specificity and sensitivity of mammography. Tibolone and transdermal estro-progestagenic therapy increase the MBD to a significantly lower degree than the oral HT.